SOCIOLINGUISTICS ANALYSIS OF TABOO WORDS IN MINAHASA DISTRICT KOMBI - Nonutu, B. Imanuel Rekhab; Oroh, Elisabeth Z; Andries, Fivy A (Journal of English Culture, Language, Literature and Education, 2021)
This research aims to: 1 Identifying and classifying types of taboo words in Kombi District Minahasa Regency 2 Knowing the function of people using taboo words in Kombi District Minahasa Regency This research uses qualitative research The subjects in this study were 15 adults aged at least 20 60 years in Kombi District especially in the villages where the research was conducted namely in Lalumpe Ranowangko Rerer Makalisung and Kalawiran villages And the main instrument in this research is the researcher himself using the Technique of Observation Interview Documentation and Questionnaire Data were analyzed using sociolinguistics analysis Research result: 1 Types of taboo words in Kombi District Minahasa Regency have 30 types of taboo words that are still remembered and used by several people in villages in Kombi District 2 The functions of taboo words in Kombi District Minahasa Regency includes an expression of annoyance as an emotional outlet and also as an expression of greeting to friends or relatives who are already familiar for some people < p>